Models of socio-cyber-physical systems security - Yevseiev, Serhii; Khokhlachova, Yuliia; Ostapov, Serhii; Laptiev, Oleksandr; Korol, Olha; Milevskyi, Stanislav; Milov, Oleksandr; Pohasii, Serhii; Melenti, Yevgen; Hrebeniuk, Vitalii; Havrylova, Alla; Herasуmov, Serhii; et al. (PC TECHNOLOGY CENTER, 2023)
The monograph discusses the methodology for cooperative conflict interaction modeling of security system agents. The concept of modeling the structure and functioning of the security system of critical infrastructure facilities is demonstrated. The method for assessing forecast of social impact in regional communities is presented. Counteracting the strategic manipulation of public opinion in decision-making by actors of social networking services based on the conceptual model for managed self-organization in social networking services are developed. Algorithms for thinning the critical infrastructure identification system and their software are implemented. The monograph is intended for teachers, researchers and engineering staff in the field of cybersecurity, information technology, social engineering, communication systems, computer technology, automated control systems and economic information security, as well as for adjuncts, graduate students and senior students of relevant specialties.
Keywords: monograph; security; models security; socio-cyber-physical systems; computing resources; business structure